Corpo Universo: uma poética das constelações compositivas como estudo e reflexão do corpo na atuação teatral - PARAGUASSU, Renan Delmontt Souza (Universidade Federal do Pará, 2019)
The research Body Universe: a poetic of the compositive constellations as study and reflection of the body in theatrical acting has as objective understand what happens in my Body/Me along the moment of acting. To do so, I venture myself as a artist-researcher, I come to understand that acting is phenomenon experienced by the actor during their creative works, that occurs inside and outside the scene. The search for this comprehension took me to dive in lived artistic memories and experiences as actor, also I had to observe, in terms of equivalent feelings, what goes on with other people that I work with and others that I have watched. The investigation is fundamental, theoryc-methodologicaly, in Phenomenology, the science the investigate the experience of consciousness since its basic levels, the sensitive, the most elaborate, and the conscious itself. Tooked as authors in this field of knowledge, the German Georg Hegel(1770-1831) and the French Gaston Bachelard (1884-1972), because he was interested in conscience of the phenomenon of creation and scenic acting immersed in the field poetic artistic, the Merleau-Ponty (1908-1961) to reflect about the present space of my Body/Me and its scenic significance from the relationship with other bodies actors/spectators, the French philosopher and sociologist Henri-Pierre Jeudy (1945-) for discussion of body as object or artistic support. On the creative processes, the Brazilian professor Sonia Rangel (1948-) helps me to understand the process as an fountain of recreation and fomentation of several layers in creation, having the memory as propeller of revisitations. In The study about the art of the actor, the Russian actor, pedagogue and director Constantin Stanislavski (1968- 1936), the also Russian actor Richard Boleslavski (1989-1967) and the director and actor Eugenio Kusnet (1898-1975) they contribute for the discussion where technique and sensibility, conscious and unconscious walk helping handing each other during the act of acting, the Italian director Eugenio Barba (1995) for the processes and rules the influence the culture and daily in which the actor is living, the polonaise director Jerzy Grotowski (1933- 1999) and the Brazilian actor Carlos Simioni (1958-) for the understanding of the importance of training as continuous preparation of the body as foundation to the creation. I decided to focus on a methodology based on the research phenomenon. with allows the construction and reflection of the poetical work starting from the multiple internal experiences, focusing on the material that comes from the conscience in front of the practices and trajectories on plays, articulating with the psychophysical training.